RECLAIMING FAMILY VALUES IN MODERN SOCIETY: PLACING FUNCTIONAL MEANING ON THE HADITH OF MĀLIK IBN AL-HUWAYRITH - Moh. Amiril Mukminin; Abubakar Yokobu; Hasanah Hasanah; Sukandi Sukandi (LP2M Universitas Ibrahimy, 2023)
The contemporary reality of society often neglects the significance of family life while prioritizing economic pursuits, religious endeavors, and missionary activities. As evident in the narrations, it disregard for Islamic values raises the relevance of recognizing the family's precedence over the imperative to engage in Islamic causes, as emphasized in the Hadith narrated by Mālik ibn al-Huwayrith. This study aims to extract the essence of the Hadith to address contemporary challenges in da'wah and religious deepening potential catalysts for family abandonment. This research method uses a qualitative approach with a hermeneutical model in data analysis; the research reveals that Mālik's allegiance, even posthumously, signifies his inclination to remain in the City of Hijrah for the advancement of Islam, a disposition the Prophet